Community Structure and Function of High-Temperature Chlorophototrophic Microbial Mats Inhabiting Diverse Geothermal Environments - Inskeep, William P.; Klatt, Christian G.; Herrgard, Markus J.; Jay, Zackary J.; Rusch, Douglas B.; Tringe, Susannah G.; Parenteau, M. Niki; Ward, David M.; Boomer, Sarah M.; Bryant, Donald A.; Miller, Scott R. (Frontiers in Microbiology, 2013)
Six phototrophic microbial mat communities from different geothermal springs (YNP) were studied using metagenome sequencing and geochemical analyses. The primary goals of this work were to determine differences in community composition of high-temperature phototrophic mats distributed across the Yellowstone geothermal ecosystem, and to identify metabolic attributes of predominant organisms present in these communities that may correlate with environmental attributes important in niche differentiation. Random shotgun metagenome sequences from six phototrophic communities (average ∼53 Mbp/site) were subjected to multiple taxonomic, phylogenetic, and functional analyses. All methods, including G + C content distribution, MEGAN analyses, and oligonucleotide frequency-based clustering, provided strong support for the dominant community members present in each site. Cyanobacteria were only observed in non-sulfidic sites; de novo assemblies were obtained for Synechococcus-like populations at Chocolate Pots (CP_7) and Fischerella-like populations at White Creek (WC_6). Chloroflexi-like sequences (esp. Roseiflexus and/or Chloroflexus spp.) were observed in all six samples and contained genes involved in bacteriochlorophyll biosynthesis and the 3-hydroxypropionate carbon fixation pathway. Other major sequence assemblies were obtained for a Chlorobiales population from CP_7 (proposed family Thermochlorobacteriaceae), and an anoxygenic, sulfur-oxidizing Thermochromatium-like (Gamma-proteobacteria) population from Bath Lake Vista Annex (BLVA_20). Additional sequence coverage is necessary to establish more complete assemblies of other novel bacteria in these sites (e.g., Bacteroidetes and Firmicutes); however, current assemblies suggested that several of these organisms play important roles in heterotrophic and fermentative metabolisms. Definitive linkages were established between several of the dominant phylotypes present in these habitats and important functional processes such as photosynthesis, carbon fixation, sulfur oxidation, and fermentation.